Fatty Acid and Amino Acid Composition of Marine Eels Congresox talabanoides and Thyrsoidea macrura from Parangipettai Coastal Waters - M. Kalaiselvam, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Fatty Acid and Amino Acid Composition of Marine Eels Congresox talabanoides and Thyrsoidea macrura from Parangipettai Coastal Waters